Antileishmanial activity of a mixture of Tridax procumbens and Allium sativum in mice - Gamboa-Leon Rubi; Vera-Ku Marina; Peraza-Sanchez Sergio R.; Ku-Chulim Carlos; Horta-Baas Aurelio; Rosado-Vallado Miguel (Parasite, 2014)
We tested a mixture of Tridax procumbens, known for its direct action against Leishmania mexicana, and Allium sativum, known for its immunomodulatory effect, as an alternative to treat cutaneous leishmaniasis. Acute oral toxicity was tested with the Up-and-Down Procedure (UDP) using a group of healthy mice administered with either T. procumbens or A. sativum extracts and compared with a control group. Liver injury and other parameters of toxicity were determined in mice at day 14. The in vivo assay was performed with mice infected with L. mexicana promastigotes and treated with either a mixture of T. procumbens and A. sativum or each extract separately. The thickness of the mice’s footpads was measured weekly. After the 12-week period of infection, blood samples were obtained by cardiac puncture to determine the total IgG, IgG1 and IgG2a immunoglobulins by a noncommercial indirect ELISA. We showed that the mixture of T. procumbens and A. sativum extracts was better at controlling L. mexicana infection while not being toxic when tested in the acute oral toxicity assay in mice. An increase in the ratio of IgG2a/IgG1 indicated a tendency to raise a Th1-type immune response in mice treated with the mixture. The mixture of T. procumbens and A. sativum extracts is a promising natural treatment for cutaneous leishmaniasis and its healing effects make it a good candidate for a possible new phytomedicine.